DETEKSI DAN ANALISIS EKSPRESI TRANSGEN (PhGH) PADA IKAN LELE DUMBO (Clarias gariepinus) TRANSGENIK F3 (Detection and Analysis Expression of transgene (PhGH) in Dumbo Catfish (Clarias gariepinus) Transgenic F3) - Fery Jaksen Sihotang; Budi Utomo; Indra Lesmana; Huria Marnis (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Fisheries output need tobe increased to meet the rising demands for fish incomingyears as the increasing of human population. Biotechnology approach has used forincreasing production on aquaculture sector. One of the advances biotechnologies thatused for aquaculture development is transgens technology. Transgenic fish is a speciesthat experience alteration of genetic structure that introduced from other organisms,with the result that change the their genetic function in accordance with the introducedgene. One of the things that support the development of transgenic fish strain formationis the ability of individual transgenic to bequeath the transgenes to the next generation,so that the genetic trait target genes stable in the resulting offspring. This study aims todetect and determine the expression of growth hormone gene (PhGH) on dumbo catfish(Clarias gariepinus) transgenic F3. Transgene detection performed on embryos andlarvae of catfish transgenic F3 using PCR with primers ACT 107 and PhGH2.Transgene expression was analyzed by using reverse transcriptase polymerase chainreaction (RT-PCR) methods with primers β-actin and ACT 107 and PhGH2. Theresults showed that the transgene was detected in some of the embryos and larvaeaccording to Mendel principle. β-actin primer amplification compared to primary ACT107 and PhGH2 showed that transgene can be expressed in some of the embryos andlarvae.Keywords: biotechnology, aquaculture, transgenic, detection, expression, growthhormone